2022
DOI: 10.1136/bmjgh-2021-007077
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional estimates of maternal near miss: a systematic review, meta-analysis and experiences with application

Abstract: IntroductionMaternal near miss (MNM) is a useful means to examine quality of obstetric care. Since the introduction of the WHO MNM criteria in 2011, it has been tested and validated, and is being used globally. We sought to systematically review all available studies using the WHO MNM criteria to develop global and regional estimates of MNM frequency and examine its application across settings.MethodsWe conducted a systematic review by implementing a comprehensive literature search from 2011 to 2018 in six dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 75 publications
0
8
0
1
Order By: Relevance
“…While most have healthy deliveries, 20%-30% undergo a highly stressful childbirth experience. 1,2 A significant minority experience potentially lifethreatening events and even maternal "near-miss" (nearly escaping death) in relation to childbirth, with rising rates in the U.S. 3 Increasing evidence reveals that women can develop post-traumatic stress disorder in response to childbirth (CB-PTSD). 4 Maternal CB-PTSD is estimated to occur in 3%-6% of the postpartum population 5,6 and in nearly 20% of those who experience complicated deliveries.…”
Section: Introductionmentioning
confidence: 99%
“…While most have healthy deliveries, 20%-30% undergo a highly stressful childbirth experience. 1,2 A significant minority experience potentially lifethreatening events and even maternal "near-miss" (nearly escaping death) in relation to childbirth, with rising rates in the U.S. 3 Increasing evidence reveals that women can develop post-traumatic stress disorder in response to childbirth (CB-PTSD). 4 Maternal CB-PTSD is estimated to occur in 3%-6% of the postpartum population 5,6 and in nearly 20% of those who experience complicated deliveries.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, improving the quality of care tailored to the needs of women is considered a key component of the right to health, and the route to equity and dignity for them. [5][6][7] Despite the WHO's recommendation for having a vision beyond the numbers, facilities now have focused on physical recovery rather than psychological and emotional impact on women. 8 Recent studies of near-misses from around the world have drawn attention to the negative psychological impact of maternal morbidities.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Moreover, improving the quality of care tailored to the needs of women is considered a key component of the right to health, and the route to equity and dignity for them. 5 - 7 …”
Section: Introductionmentioning
confidence: 99%
“…5 Even a good news recent systemic review and metaanalysis of the WHO MNM criteria uptake in LIC showed that despite good uptake in these countries enabling some intercountry comparisons, there was still the need in individual countries for contextual adaptations. 6 Surely the conversation needs to change. A search for peerreviewed research on SMM and MNM reviews revealed 100s of articles on defining, re-defining, counting, rates, associated factors, preventability, and opportunities for improvements.…”
mentioning
confidence: 99%
“…The authors concluded that global standardising was ‘not feasible at this time’ 5 . Even a good news recent systemic review and meta‐analysis of the WHO MNM criteria uptake in LIC showed that despite good uptake in these countries enabling some intercountry comparisons, there was still the need in individual countries for contextual adaptations 6 …”
mentioning
confidence: 99%